Analisis Nilai Indeks Penggunaan Air Dan Kualitas Air Pada Sub Das Stasiun Pasir Pangaraian - Oktavia, Gumi; Handayani, Yohanna Lilis; Siswanto, Siswanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Watershed management can be divided into five criteria, namely land use, water system, social, economic and institutional. The study describes the water management criteria in thesub-watershed of Pasir Pangaraian station, with indicators namely water utilization index and water quality. The research objective is to analyze the results of the parameters under study, and determine the classification of these parameters based on the Director General's Regulation on Land Rehabilitation and Forestry: P.04 / V-SET / 2009. In this study, the analysis and calculation stages of the river water system are carried out with indicators of river water discharge. The results showed that the water utilization index (IPA) was categorized as good with a value of 2,4x10-5 and water quality from year 2014-2017 is categorized as good. From the results of these two parameters, the criteria for the watersystem in the sub-watershed of Pasir Pangaraian station are classified as good.Keywords: Stream System, Water utilization Index and Water Quality.